Graphene-based conductive color paste as well as preparation method and application thereof
By controlling the particle size distribution of conductive fillers and adding high-conductive graphene, a three-dimensional conductive network is constructed, which solves the problems of poor conductivity and insufficient stability of carbon-based conductive color paste, and achieves graphene-based conductive color paste with excellent conductivity and stability, which is suitable for a variety of high-end materials.
Patent Information
- Application Number
- CN202311355554.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the carbon-based conductive color paste has poor conductivity, uneven dispersion of powdered graphene in solvents, easy to agglomerate, and insufficient stability, which limits its application in the mid-to-high-end fields.
By controlling the particle size distribution of conductive fillers, the graphene sheet forms a two-dimensional conductive surface, and other conductive fillers increase the filling coefficient, build a three-dimensional conductive network, and combine the addition of highly conductive graphene to optimize the conductivity and dispersion performance.
It has achieved graphene-based conductive color paste with excellent conductivity, excellent stability, good compatibility and low VOC emissions. It is suitable for antistatic coatings, conductive inks, and antistatic composite materials. The material surface resistance can be achieved by adding a small amount of 103Ω/sq~106Ω/sq.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of graphene, and more particularly to a graphene-based conductive color paste and a preparation method and application thereof. Background Art
[0002] Conductive color paste is a conductive paste composed of conductive filler, dispersant and matrix resin with a certain dispersion stability. When preparing antistatic materials, by controlling the amount of conductive color paste added, antistatic materials with different antistatic levels can be obtained. Compared with directly adding conductive fillers, the addition of conductive color paste can effectively inhibit the agglomeration and phase separation of conductive fillers in the matrix material.
[0003] At present, common conductive color pastes mainly include metal-based and non-metal-based. Metal-based conductive color pastes need to add metal conductive materials such as silver, nickel, and copper. Although they have high conductivity, they have problems such as heavy metal pollution, acid and alkali corrosion resistance, and high cost, which limit their application. Carbon-based conductive color pastes are safe to use, have good biocompatibility, and can use water as a solvent, making them a hot spot for current research and development and application. However, the performance of carbon-based conductive color pastes is greatly affected by the dispersion of conductive fillers in the matrix resin. At present, the main solutions include oxidation modification, grafting modification, direct dispersion of dispersants, and polymer coating methods. Although many domestic companies and scientific research institutions have developed many water-based carbon-based conductive color pastes, the conductivity and stability have not yet met expectations, and their application has certain limitations.
[0004] Invention patent CN102532975A discloses a universal carbon black paste and its preparation process, which uses dry chemical modification to grind the powdered conductive carbon black, and uses coupling agents and stabilizers to modify the surface of the conductive carbon black at a certain temperature to prepare a conductive color paste with good dispersion stability. However, the invention process is complicated and the conductive material carbon black used has poor conductivity, which limits its application in mid-to-high-end fields.
[0005] In the prior art, the conductivity of graphene-based conductive pigments based on redox type is poor; the dispersion stability of graphene-based conductive pigments based on physical exfoliation is poor; the amount of metal nanoparticles added in the graphene / metal nanoparticle doped conductive pigments is large and the cost is high.
[0006] Therefore, developing a carbon-based conductive color paste with excellent conductivity, excellent dispersion performance and simple preparation process is a technical challenge in this field. Summary of the invention
[0007] In order to solve the technical problems existing in the prior art, the present invention provides a graphene-based conductive color paste and a preparation method and application thereof.
[0008] The present invention prepares a graphene-based conductive color paste. By controlling the particle size distribution of the conductive filler, the graphene sheet can form a two-dimensional conductive surface. Other conductive fillers can improve the filling factor of the conductive filler in the matrix resin, and construct a three-dimensional conductive network with better conductive performance. At the same time, by adding the highly conductive graphene developed by itself, excellent conductivity can be achieved when the amount of graphene added is small. While reducing the cost, the leveling property of the color paste itself is more excellent after the amount of graphene added is reduced, and it has self-leveling performance, which is different from the traditional thixotropic slurry.
[0009] The graphene-based conductive color paste prepared by the present invention has the characteristics of excellent conductivity (square resistance), excellent stability (stable storage for 6 months without flocculation), good compatibility, low VOC emission, etc., and can be applied to antistatic coatings, conductive inks, and antistatic composite materials. By adding a small amount (1‰ to 2%), the surface resistance of the material can be increased by 10 3 Ω / sq~10 6 Ω / sq. The present invention solves the problems in the prior art such as poor conductivity of carbon-based conductive color paste, uneven dispersion of graphene powder in solvent, easy agglomeration, and poor stability of carbon-based conductive color paste.
[0010] One of the purposes of the present invention is to provide a graphene-based conductive color paste.
[0011] The graphene-based conductive color paste, based on a total mass of 100%, comprises the following components:
[0012] Conductive filler 1-25%; preferably 5-15%;
[0013] Dispersant 0.1-2%; preferably 0.5-1%;
[0014] Matrix resin 10-30%; preferably 20-30%;
[0015] The rest is solvent.
[0016] In a preferred embodiment of the present invention,
[0017] The conductive filler consists of graphene and other conductive fillers except graphene; preferably,
[0018] The graphene is powdered graphene of Chinese invention patent CN115231561A (the invention name is “a kind of powdered graphene and its preparation method and application”, and the disclosure time is October 25, 2022);
[0019] The graphene is a few-layer graphene, and more preferably has 1 to 10 layers;
[0020] The other conductive filler is at least one of conductive carbon black, conductive graphite, and carbon nanotubes;
[0021] The dispersant is at least one of fatty alcohol EO / PO block polyether;
[0022] The base resin is at least one of the cationic epoxy resins, preferably a cationic epoxy resin with an epoxy equivalent of 300 to 600; the cationic epoxy resin can be a bisphenol A type or bisphenol F type cationic epoxy resin, such as a commercially available cationic epoxy resin with one of the following grades: AX 246w / 70BG, AX 237w / 70BG, AX 250w / 75EP, 0906, DER 916; The matrix resin of the present invention can make the prepared graphene-based conductive color paste dispersed in both aqueous systems and oily systems, and is a color paste with amphiphilic properties;
[0023] The solvent comprises a first solvent, a second solvent and a third solvent; preferably, the first solvent is water; the second solvent is a fatty alcohol, preferably at least one of ethanol and isopropanol; the third solvent is a fatty ether, preferably at least one of ethylene glycol dimethyl ether, ethylene glycol monobutyl ether, propylene glycol butyl ether and propylene glycol methyl ether; further preferably, based on the total mass of the solvent as 100%, the solvent comprises:
[0024] The first solvent is 20-95%;
[0025] The second solvent is 1-60%;
[0026] The third solvent 1-30%;
[0027] More preferably, the solvent comprises:
[0028] The first solvent is 35-90%;
[0029] The second solvent is 4-50%;
[0030] The third solvent is 6-25%.
[0031] In a preferred embodiment of the present invention,
[0032] The mass ratio of the graphene to other conductive fillers is 1:(1-10), preferably 1:(1-5);
[0033] The carbon content of the graphene is ≥ 99.50wt.%, preferably 99.80-99.95wt.%;
[0034] The oxygen content of the graphene is less than 300 ppm;
[0035] The graphene powder conductivity is ≥800S / cm;
[0036] The molar ratio of EO to PO in the fatty alcohol EO / PO block polyether is 1:(0.8-3);
[0037] The weight average molecular weight of the fatty alcohol EO / PO block polyether is 348-552 g / mol.
[0038] The fatty alcohol EO / PO block polyether is added in the form of an aqueous solution, preferably, the fatty alcohol EO / PO block polyether is prepared into an aqueous solution using part of the solvent in the graphene-based conductive color paste and then added.
[0039] The fatty alcohol EO / PO block polyether can be a commercially available product that meets the requirements, or the fatty alcohol EO / PO block polyether that meets the above requirements can be synthesized using the existing method.
[0040] The dispersant has the following advantages: (1) low surface tension (lower than powdered graphene), easy to infiltrate and spread on the graphene surface; (2) non-ionic dispersant, no mutual electrostatic interaction between graphene and the dispersant; (3) the terminal initiator is a multi-branched alcohol, which can avoid foaming (usually surfactants with low specific surface area are prone to foaming).
[0041] In a preferred embodiment of the present invention,
[0042] The D10 particle size of the conductive filler is 70-150nm, the D50 particle size is 2-3μm, and the D90 particle size is 5-6μm; the conductive filler of the present invention is composite and must contain graphene. The graphene sheet can form a two-dimensional conductive surface, and at the same time, a certain proportion of other conductive fillers are matched, and the optimal particle size distribution confirmed by the above experiment is adopted. Other conductive fillers can construct a three-dimensional conductive network combining "point-surface" or "line-surface" with the "surface" of the graphene sheet, which can improve the conductivity of the product.
[0043] The specific surface area of the conductive filler is 30 to 65 m 2 / g;
[0044] The oil absorption value of the conductive filler is 200 to 350 ml / 100 g;
[0045] The specific surface area and oil absorption value of the conductive filler will affect its processing performance. Usually, the specific surface area and the oil absorption value are positively correlated. If the oil absorption value of the conductive filler is too large, the viscosity of the prepared slurry will increase sharply, the leveling property will be extremely poor, and a uniform ink coating cannot be formed. At the same time, too large an oil absorption value will also limit the amount of conductive filler added, resulting in a low limiting conductivity.
[0046] In a preferred embodiment of the present invention,
[0047] The non-volatile matter mass content of the graphene-based conductive color paste is 25-40%, preferably 30-35%;
[0048] The viscosity of the graphene-based conductive color paste is 1800-2500 cps.
[0049] The second object of the present invention is to provide a method for preparing a graphene-based conductive paste, comprising the following steps:
[0050] (1) According to the component ratio, the conductive filler, the dispersant, and the solvent are mixed and then subjected to high pressure homogenization to obtain a mixed solution;
[0051] (2) According to the component ratio, the mixed solution obtained in step (1) is evenly mixed with the base resin to obtain the graphene-based conductive color paste.
[0052] In a preferred embodiment of the present invention,
[0053] Step (1),
[0054] The conductive filler is composed of graphene and other conductive fillers except graphene, and the graphene is sand-milled; preferably, the graphene is sand-milled for 10 to 30 minutes with a sand mill, the rotation speed of the sand mill is 1500 to 2500 rpm, and the solvent for sand milling is water or N-methylpyrrolidone;
[0055] The pressure of the high-pressure homogenization treatment is 100-200 MPa, preferably 120-150 MPa;
[0056] The high pressure homogenization treatment time is 10 to 40 minutes, preferably 10 to 25 minutes.
[0057] In a preferred embodiment of the present invention,
[0058] Step (2),
[0059] The mixing method is high-speed shear dispersion, the rotation speed of the high-speed shear dispersion is 1200-1500 rpm, and the dispersion time is 20-40 minutes.
[0060] The third object of the present invention is to provide a graphene-based conductive color paste obtained by the above preparation method.
[0061] A fourth object of the present invention is to provide a graphene-based conductive color paste for use in antistatic coatings, conductive inks, and antistatic composite materials.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] The present invention solves the problems in the prior art such as poor conductivity of carbon-based conductive paste, uneven dispersion of powdered graphene in solvent, easy agglomeration, and poor stability of carbon-based conductive paste, and prepares a graphene-based conductive paste with the characteristics of excellent conductivity (sheet resistance), excellent stability (stable storage for 6 months without flocculation), good compatibility, low VOC emission, etc., which can be applied to antistatic coatings, conductive inks, and antistatic composite materials. By adding a small amount (1‰ to 2%), the surface resistance of the material can be reduced by 10 3 Ω / sq~10 6 Ω / sq.
[0064] The preparation processes of the present invention are all physical processes, without the use of chemical reagents, are environmentally friendly, and can be scaled up. DETAILED DESCRIPTION
[0065] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0066] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0067] In the following examples and comparative examples, the room temperature refers to 25°C.
[0068] In the embodiments and comparative examples,
[0069] The graphene is powdered graphene prepared by the laboratory according to the record of Chinese invention patent CN115231561A (the invention name is "a kind of powdered graphene and its preparation method and application", the disclosure time is October 25, 2022); wherein,
[0070] The powdered graphene in Examples 1 to 2, 4 to 5 and Comparative Example 1 is prepared with reference to Example 1 of Patent CN115231561A, and the difference from Example 1 of Patent CN115231561A is that the expansion multiples of the expandable graphite powder in step (1) are different, and after expansion treatment, pre-expanded graphite with an expansion multiple of 150 times is obtained; except for the above differences, other conditions are the same as those in Example 1 of Patent CN115231561A, and a powdered graphene A with 3 to 5 layers is obtained, and its carbon content is 99.9%, the oxygen content is 80ppm, and the powder conductivity is 1460S / cm.
[0071] The powder graphene in Example 3 is prepared with reference to Example 1 of patent CN115231561A. The difference from Example 1 of patent CN115231561A is that the expandable graphite powder (from Aladdin Reagent Company) is replaced by YH-200 (Qingdao Yanhai Carbon Materials Co., Ltd.) expandable graphite powder with a lower carbon content; except for the above differences, other conditions are the same as those in Example 1 of patent CN115231561A, and powder graphene B with 3 to 5 layers is obtained. The carbon content is 99.5%, the oxygen content is 220ppm, and the powder conductivity is 1050S / cm.
[0072] The powder graphene in Comparative Example 2 is prepared with reference to Example 1 of patent CN115231561A. The difference from Example 1 of patent CN115231561A is that the expandable graphite powder is replaced by flake graphite with a carbon content of 90% (Qingdao Yanhai Carbon Materials Co., Ltd., 100 mesh), and a powder graphene C with 5-8 layers of graphene is obtained. The carbon content is 90.5%, the oxygen content is 2%, and the powder conductivity is 350S / cm.
[0073] Except for graphene, the raw materials in the examples and comparative examples are all conventional commercially available raw materials, among which:
[0074] The base resin was purchased from Allnex Resins (China) Co., Ltd. AX 246w / 70BG, viscosity is 12000~13000mPa·s, epoxy equivalent is 450~500.
[0075] The dispersant is fatty alcohol EO / PO block polyether with a weight average molecular weight of 450 g / mol.
[0076] The conductive carbon black is Super P Li from IMERYS.
[0077] Test method:
[0078] Square resistance: tested by ST2258C multifunctional digital four-probe tester of Suzhou Jingge Electronics Co., Ltd. The test process is carried out in accordance with GB / T 1552-1995.
[0079] Carbon content of graphene: DB32 / T 3595-2019;
[0080] Oxygen content of graphene: DB32 / T 3595-2019;
[0081] Graphene powder conductivity: T / GDASE 0011-2020;
[0082] Specific surface area of conductive filler: GB / T 10722-2003;
[0083] Oil absorption value of conductive filler: GB / T 3780.2-2007;
[0084] Non-volatile matter mass content of conductive color paste: GB / T 17473.1-2008;
[0085] Viscosity of graphene-based conductive color paste: GB / T 17473.5-2008.
[0086] The parts in the following examples and comparative examples are all parts by weight;
[0087] Example 1
[0088] (1) Using water as solvent, the self-made graphene was sand-milled for 20 minutes with a nano sand mill at a speed of 2000 rpm to make its particle size smaller. In parts by mass, 1.5 parts of the ground self-made graphene A, 3.5 parts of conductive carbon black, 60 parts of deionized water, 3 parts of isopropanol, 6 parts of propylene glycol butyl ether, and 1 part of dispersant were taken, and after simple stirring and dispersion, they were added into a high-pressure homogenizer, and treated at a pressure of 150 MPa for 25 minutes to obtain a graphene-based conductive dispersion.
[0089] (2) Add 25 parts of matrix resin into the above graphene conductive dispersion, and stir at 1200 rpm for 30 minutes to obtain a graphene-based conductive color paste.
[0090] The number of layers of powdered graphene is 3 to 5. According to the DB32 / T 3595-2019 standard, its carbon content is 99.9%, and its oxygen content is 80ppm. According to the T / GDASE 0011-2020 standard, its powder conductivity is 1460S / cm.
[0091] The conductive filler composed of graphene and conductive carbon black has a specific surface area of 32m 2 / g, oil absorption value is 228ml / 100g, D10 is 85nm, D50 is 3μm, and D90 is 5μm.
[0092] The weight average molecular weight of the dispersant in the conductive color paste is 450g / mol, the EO / PO ratio is 1:1.14, and the cationic resin is AX 246w / 70BG, epoxy equivalent weight is 450-500.
[0093] The mass content of non-volatile matter in the conductive color paste is 30%, and the viscosity of the graphene-based conductive color paste is 2000cps. 10ml of the above graphene-based conductive color paste is placed in a sample bottle, and the surface liquid of the paste is taken at 1 month, 2 months, and 3 months to test the mass of its non-volatile matter by evaporation method. The test results show that at 1 month, 2 months, and 3 months, the mass of non-volatile matter on the surface of the above slurry is 30%, 30%, and 29.8%.
[0094] Take 5 ml of the above conductive color paste and place it on the PET substrate. After 10 minutes, when the color paste is dry on the surface, place the above film in an oven at 80°C and dry for 2 hours. After the sample is completely dry, randomly select 5 points on the film and test its thickness with a micrometer. The test results show that the thickness of the five points are 120μm, 121μm, 121μm, 118μm, and 120μm, respectively, with good consistency.
[0095] Take 5 ml of the above conductive color paste and use a scraping paint to scrape a 5 cm×5 cm thin film on an acrylic plate. Then place the coating in an 80°C oven and dry it for 90 minutes. The sheet resistance of the film is measured by a four-probe tester and is 12 mΩ / sq (film thickness 25 μm).
[0096] Example 2
[0097] (1) Using water as solvent, the self-made graphene was sand-milled for 20 minutes with a nano sand mill at a speed of 2000 rpm to make its particle size smaller. In parts by mass, 6 parts of the ground self-made graphene A, 9 parts of conductive carbon black, 25 parts of deionized water, 29.5 parts of isopropanol, 10 parts of propylene glycol butyl ether, and 0.5 parts of dispersant were taken, and after simple stirring and dispersion, they were added into a high-pressure homogenizer, and treated at a pressure of 200 MPa for 20 minutes to obtain a graphene-based conductive dispersion.
[0098] (2) Add 20 parts of matrix resin into the above graphene conductive dispersion, and stir at 1200 rpm for 40 minutes to obtain a graphene-based conductive color paste.
[0099] The graphene powder used is the same as that in Example 1.
[0100] The conductive filler composed of graphene and conductive carbon black has a specific surface area of 40m2 / g, oil absorption value is 296ml / 100g, D10 is 85nm, D50 is 3μm, and D90 is 5μm.
[0101] The dispersant used is the same as in Example 1.
[0102] Cationic resin AX 246w / 70BG, epoxy equivalent weight is 450-500.
[0103] The non-volatile matter content of the conductive color paste was measured to be 35%, and the viscosity of the graphene-based conductive color paste was 2400cps. 10ml of the graphene-based conductive color paste was placed in a sample bottle, and the surface liquid of the paste was taken at 1 month, 2 months, and 3 months to test the non-volatile matter mass by evaporation method. The measurement results showed that at 1 month, 2 months, and 3 months, the surface non-volatile matter mass of the above-mentioned paste was 35%, 35%, and 35%.
[0104] Take 5 ml of the above conductive color paste and place it on the PET substrate. After 10 minutes, when the color paste is dry on the surface, place the above film in an oven at 80°C and dry for 2 hours. After the sample is completely dry, randomly select 5 points on the film and test its thickness with a micrometer. The test results show that the thickness of the five points are 180μm, 179μm, 180μm, 182μm, and 180μm, respectively, with good consistency.
[0105] Take 2 ml of the above conductive color paste and use a scraping paint to scrape a 5 cm×5 cm thin film on an acrylic plate. Then place the coating in an 80°C oven and dry it for 90 minutes. The square resistance of the film is measured by a four-probe tester and is 15 mΩ / sq (film thickness 25 μm).
[0106] Example 3
[0107] (1) Using water as solvent, the self-made graphene was sand-milled for 20 minutes at a speed of 2000 rpm using a nano sand mill to make its particle size smaller. In parts by mass, 2 parts of the ground self-made graphene B, 2 parts of conductive carbon black, 45 parts of deionized water, 5 parts of isopropanol, 15 parts of propylene glycol butyl ether, and 1 part of dispersant were taken, and after simple stirring and dispersion, they were added into a high-pressure homogenizer, and treated at a pressure of 150 MPa for 25 minutes to obtain a graphene-based conductive dispersion.
[0108] (2) Add 30 parts of matrix resin into the above graphene conductive dispersion, and stir at 1200 rpm for 30 minutes to obtain a graphene-based conductive color paste.
[0109] The graphene used is powdered graphene with 3 to 5 layers. According to the DB32 / T 3595-2019 standard, its carbon content is 99.5%, and its oxygen content is 220ppm. According to the T / GDASE 0011-2020 standard, its powder conductivity is 1050S / cm.
[0110] The conductive filler composed of graphene and conductive carbon black has a specific surface area of 30m 2 / g, oil absorption value is 200ml / 100g, D10 is 85nm, D50 is 3μm, and D90 is 6μm.
[0111] The dispersant used is the same as that in Example 1.
[0112] Cationic resin AX 246w / 70BG, epoxy equivalent weight is 450-500.
[0113] The mass content of non-volatile matter in the conductive color paste is 34%, and the viscosity of the graphene-based conductive color paste is 1840cps. 10ml of the above graphene-based conductive color paste was placed in a sample bottle, and the surface liquid of the paste was taken at 1 month, 2 months, and 3 months to test the mass of its non-volatile matter by evaporation method. The test results show that at 1 month, 2 months, and 3 months, the mass of non-volatile matter on the surface of the above slurry is 34%, 34%, and 34%.
[0114] Take 5 ml of the above conductive color paste and place it on the PET substrate. After 10 minutes, when the color paste is dry on the surface, place the above film in an oven at 80°C and dry for 2 hours. After the sample is completely dry, randomly select 5 points on the film and test its thickness with a micrometer. The test results show that the thickness of the five points are 100μm, 101μm, 100μm, 100μm, and 100μm, respectively, with good consistency.
[0115] Take 5 ml of the above conductive color paste and use a scraping paint to scrape a 5 cm×5 cm thin film on an acrylic plate. Then place the coating in an 80°C oven and dry it for 90 minutes. The sheet resistance of the film is measured by a four-probe tester and is 16 mΩ / sq (film thickness 25 μm).
[0116] Example 4
[0117] (1) Using water as solvent, the self-made graphene was sand-milled for 20 minutes with a nano sand mill at a speed of 2200 rpm to make its particle size smaller. In parts by mass, 2 parts of the ground self-made graphene A, 10 parts of conductive carbon black, 50 parts of deionized water, 10 parts of isopropanol, 5 parts of propylene glycol butyl ether, and 1 part of dispersant were taken, and after simple stirring and dispersion, they were added into a high-pressure homogenizer and treated at a pressure of 100 MPa for 30 minutes to obtain a graphene-based conductive dispersion.
[0118] (2) Add 22 parts of matrix resin into the above graphene conductive dispersion, and stir at 1200 rpm for 30 minutes to obtain a graphene-based conductive color paste.
[0119] The graphene powder used is the same as that in Example 1.
[0120] The conductive filler composed of graphene and conductive carbon black has a specific surface area of 56m 2 / g, oil absorption value is 340ml / 100g, D10 is 70nm, D50 is 3μm, and D90 is 5μm.
[0121] The dispersant used is the same as in Example 1.
[0122] Cationic resin AX 246w / 70BG, epoxy equivalent weight is 450-500.
[0123] The mass content of non-volatile matter in the conductive color paste is 34%, and the viscosity of the graphene-based conductive color paste is 2400cps. 10ml of the above graphene-based conductive color paste was placed in a sample bottle, and the surface liquid of the paste was taken at 1 month, 2 months, and 3 months to test the mass of its non-volatile matter by evaporation method. The test results show that at 1 month, 2 months, and 3 months, the mass of the surface non-volatile matter of the above slurry is 34%, 34%, and 34%.
[0124] Take 5 ml of the above conductive color paste and place it on the PET substrate. After 10 minutes, when the color paste is dry on the surface, place the above film in an 80°C oven and dry for 2 hours. After the sample is completely dry, randomly select 5 points on the film and test its thickness with a micrometer. The test results show that the thickness of the five points are 200μm, 199μm, 200μm, 201μm, and 200μm, respectively, with good consistency.
[0125] Take 2 ml of the above conductive color paste and use a scraping paint to scrape a 5 cm×5 cm thin film on an acrylic plate. Then place the coating in an 80°C oven and dry it for 90 minutes. The square resistance of the film is measured by a four-probe tester and is 15 mΩ / sq (film thickness 25 μm).
[0126] Example 5
[0127] (1) Using water as solvent, the self-made graphene was sand-milled for 20 minutes with a nano sand mill at a speed of 2000 rpm to make its particle size smaller. In parts by mass, 1.5 parts of the ground self-made graphene A, 3.5 parts of conductive carbon black, 55 parts of deionized water, 3 parts of isopropanol, 6 parts of propylene glycol butyl ether, and 1 part of dispersant were taken, and after simple stirring and dispersion, they were added into a high-pressure homogenizer, and treated at a pressure of 120 MPa for 10 minutes to obtain a graphene-based conductive dispersion.
[0128] (2) Add 30 parts of matrix resin into the above graphene conductive dispersion, and stir at 1500 rpm for 20 minutes to obtain a graphene-based conductive color paste.
[0129] The graphene powder used is the same as that in Example 1.
[0130] The conductive filler composed of graphene and conductive carbon black has a specific surface area of 32m 2 / g, oil absorption value is 228ml / 100g, D10 is 85nm, D50 is 3μm, and D90 is 5μm.
[0131] The dispersant used is the same as in Example 1.
[0132] The mass content of non-volatile matter in the conductive color paste is 35%, and the viscosity of the graphene-based conductive color paste is 2000cps. 10ml of the above graphene-based conductive color paste is placed in a sample bottle, and the surface liquid of the paste is taken at 1 month, 2 months, and 3 months to test the mass of its non-volatile matter by evaporation method. The test results show that at 1 month, 2 months, and 3 months, the mass of the surface non-volatile matter of the above slurry is 35%, 35%, and 35%.
[0133] Take 5 ml of the conductive color paste in Example 5 and place it on a PET substrate. After 10 minutes, when the color paste is dry on the surface, place the film in an oven at 80°C and dry for 2 hours. After the sample is completely dried, 5 points are randomly selected on the film and the thickness is tested with a micrometer. The test results show that the thickness of the five points is 130μm, 130μm, 131μm, 129μm, and 130μm, respectively, with good consistency.
[0134] Take 5 ml of the above conductive color paste and use a scraping paint to scrape a 5 cm×5 cm thin film on an acrylic plate. Then place the coating in an 80°C oven and dry it for 90 minutes. The square resistance of the film is measured by a four-probe tester and is 20 mΩ / sq (film thickness 25 μm).
[0135] Comparative Example 1
[0136] The difference from Example 1 is that the self-made graphene A is not sanded by a sand mill, but is directly mixed with conductive carbon black to obtain a conductive filler, and then mixed with other components;
[0137] The specific surface area of the conductive filler composed of graphene and conductive carbon black is measured to be 28 m 2 / g, oil absorption value is 200ml / 100g, D10 is 200nm, D50 is 6μm, D90 is 15μm;
[0138] Except for the above differences, other conditions of Comparative Example 1 are the same as those of Example 1 to obtain a graphene-based conductive color paste.
[0139] The mass content of non-volatile matter in the conductive color paste is 30%, and the viscosity of the graphene-based conductive color paste is 1600cps. 10ml of the above graphene-based conductive color paste was placed in a sample bottle, and the surface liquid of the paste was taken at 1 month, 2 months, and 3 months to test the mass of its non-volatile matter by evaporation method. The test results show that at 1 month, 2 months, and 3 months, the mass content of non-volatile matter in the surface layer of the above slurry is 30%, 29.9%, and 29.6%.
[0140] Take 5 ml of the above conductive color paste and place it on the PET substrate. After 10 minutes, when the color paste is dry on the surface, place the above film in an oven at 80°C and dry for 2 hours. After the sample is completely dry, randomly select 5 points on the film and test its thickness with a micrometer. The test results show that the thickness of the five points are 125μm, 125μm, 126μm, 122μm, and 126μm, respectively, with good consistency.
[0141] Take 5 ml of the above conductive color paste and use a scraping paint to scrape a 5 cm×5 cm thin film on an acrylic plate. Then place the coating in an 80°C oven and dry it for 90 minutes. The sheet resistance of the film is measured by a four-probe tester and is 55 mΩ / sq (film thickness 25 μm).
[0142] Comparative Example 2
[0143] The difference from Example 1 is that the graphene used is self-made graphene C,
[0144] The self-made graphene C is a powder with 5-8 layers. The carbon content is 90.5%, the oxygen content is 2%, and the powder conductivity is 350S / cm.
[0145] Except for the above differences, other conditions of Comparative Example 2 are the same as those of Example 1 to obtain a graphene-based conductive color paste.
[0146] The conductive filler composed of graphene and conductive carbon black has a specific surface area of 35m 2 / g, oil absorption value is 300ml / 100g, D10 is 80nm, D50 is 6μm, and D90 is 8μm.
[0147] The mass content of non-volatile matter in the conductive color paste is 30%, and the viscosity of the graphene-based conductive color paste is 2100cps. 10ml of the above graphene-based conductive color paste is placed in a sample bottle, and the surface liquid of the paste is taken at 1 month, 2 months, and 3 months to test the mass of its non-volatile matter by evaporation method. The test results show that at 1 month, 2 months, and 3 months, the mass of the surface non-volatile matter of the above slurry is 30%, 30%, and 30%.
[0148] Take 5 ml of the above conductive color paste and place it on the PET substrate. After 10 minutes, when the color paste is dry on the surface, place the above film in an 80°C oven and dry for 2 hours. After the sample is completely dry, randomly select 5 points on the film and test its thickness with a micrometer. The test results show that the thickness of the five points are 113μm, 113μm, 114μm, 112μm, and 110μm, respectively, with good consistency.
[0149] Take 5 ml of the above conductive color paste and use a scraping paint to scrape a 5 cm×5 cm thin film on an acrylic plate. Then place the coating in an 80°C oven and dry it for 90 minutes. The sheet resistance of the film is measured by a four-probe tester and is 650 mΩ / sq (film thickness 25 μm).
[0150] Comparative Example 3
[0151] The difference from Example 1 is that the dispersant and the dosage are different, 5 parts of commercially available BYK-9077 dispersant; the dosage of deionized water is 56 parts;
[0152] Except for the above differences, other conditions of Comparative Example 3 are the same as those of Example 1 to obtain a graphene-based conductive color paste.
[0153] The mass content of non-volatile matter in the conductive color paste is 30%, and the viscosity of the graphene-based conductive color paste is 2000cps. 10ml of the above graphene-based conductive color paste is placed in a sample bottle, and the surface liquid of the paste is taken at 1 month, 2 months, and 3 months to test the mass of its non-volatile matter by evaporation method. The test results show that at 1 month, 2 months, and 3 months, the mass content of non-volatile matter in the surface layer of the above slurry is 30%, 28.5%, and 26.2%.
[0154] Take 5 ml of the above conductive color paste and place it on the PET substrate. After 10 minutes, when the color paste is dry on the surface, place the above film in an oven at 80°C and dry for 2 hours. After the sample is completely dry, randomly select 5 points on the film and test its thickness with a micrometer. The test results show that the thickness of the five points are 135μm, 132μm, 134μm, 130μm, and 135μm, respectively, with good consistency.
[0155] Take 5 ml of the above conductive color paste and use a scraping paint to scrape a 5 cm×5 cm thin film on an acrylic plate. Then place the coating in an 80°C oven and dry it for 90 minutes. The sheet resistance of the film is measured by a four-probe tester and is 110 mΩ / sq (film thickness 25 μm).
[0156] Compared with Example 1, the particle size of the conductive filler in Comparative Example 1 is different, the graphene in Comparative Example 2 is different, and the dispersant in Comparative Example 3 is different. When the film thickness is 25 μm, the square resistance of the thin films of Example 1 and Comparative Examples 1 to 3 are 12 mΩ / sq, 55 mΩ / sq, 650 mΩ / sq, and 110 mΩ / sq, respectively. The conductive performance of Example 1 is much better than that of Comparative Examples 1 to 3, which proves that the graphene-based conductive color paste prepared by the present invention can construct a three-dimensional conductive network with better dispersion by controlling the particle size distribution of the conductive filler, using highly conductive graphene, and using a homemade dispersant, thereby achieving better conductivity.
[0157] The sheet resistance of the graphene-based conductive paste prepared in Examples 1 to 5 is 12 to 20 mΩ / sq (film thickness 25 μm), and the conductivity is good; the stability performance test data proves that the dispersion has good stability; because the amount of graphene used is low, the conductive paste has self-leveling properties; the problems of poor conductivity of carbon-based conductive paste, uneven dispersion of powdered graphene in the solvent, easy agglomeration, and poor stability of carbon-based conductive paste in the prior art are solved, and its self-leveling performance is different from that of traditional thixotropic slurries.
[0158] The graphene-based conductive color paste prepared by the present invention has the characteristics of excellent conductivity (square resistance), excellent stability (stable storage for 6 months without flocculation), good compatibility, low VOC emission, etc., and can be applied to antistatic coatings, conductive inks, and antistatic composite materials. By adding a small amount (1‰ to 2%), the surface resistance of the material can be increased by 10 3 Ω / sq~10 6 Ω / sq.
Claims
1. A graphene-based conductive color paste, based on 100% total mass, comprising the following components: Conductive filler 1-25%; preferably 5-15%; Dispersant 0.1-2%; preferably 0.5-1%; Matrix resin 10-30%; preferably 20-30%; The rest is solvent.
2. The graphene-based conductive paste according to claim 1, characterized in that: The conductive filler consists of graphene and other conductive fillers except graphene; preferably, The graphene is a few-layer graphene, more preferably with 1 to 10 layers; and / or, The other conductive filler is at least one of conductive carbon black, conductive graphite and carbon nanotubes; and / or, The dispersant is at least one of fatty alcohol EO / PO block polyether; and / or, The base resin is at least one of cationic epoxy resins, preferably a cationic epoxy resin with an epoxy equivalent of 300 to 600; and / or, The solvent comprises a first solvent, a second solvent and a third solvent; preferably, the first solvent is water; the second solvent is a fatty alcohol, preferably at least one of ethanol and isopropanol; the third solvent is a fatty ether, preferably at least one of ethylene glycol dimethyl ether, ethylene glycol monobutyl ether, propylene glycol butyl ether and propylene glycol methyl ether; further preferably, based on the total mass of the solvent as 100%, the solvent comprises: The first solvent is 20-95%; The second solvent is 1-60%; The third solvent 1-30%; More preferably, the solvent comprises: The first solvent is 35-90%; The second solvent is 4-50%; The third solvent is 6-25%.
3. The graphene-based conductive paste according to claim 2, characterized in that: The mass ratio of the graphene to other conductive fillers is 1:(1-10), preferably 1:(1-5); and / or, The carbon content of the graphene is ≥ 99.50 wt.%, preferably 99.80-99.95 wt.%; and / or, The oxygen content of the graphene is less than 300 ppm; and / or, The graphene powder conductivity is ≥800S / cm; and / or, The molar ratio of EO to PO in the fatty alcohol EO / PO block polyether is 1:(0.8-3); and / or, The weight average molecular weight of the fatty alcohol EO / PO block polyether is 348-552 g / mol.
4. The graphene-based conductive paste according to claim 1, characterized in that: The conductive filler has a D10 particle size of 70 to 150 nm, a D50 particle size of 2 to 3 μm, and a D90 particle size of 5 to 6 μm; and / or, The specific surface area of the conductive filler is 30 to 65 m 2 / g; and / or, The oil absorption value of the conductive filler is 200 to 350 ml / 100 g.
5. The graphene-based conductive paste according to any one of claims 1 to 4, characterized in that: The non-volatile matter mass content of the graphene-based conductive color paste is 25-40%, preferably 30-35%; and / or, The viscosity of the graphene-based conductive color paste is 1800-2500 cps.
6. A method for preparing a graphene-based conductive color paste according to any one of claims 1 to 5, comprising the following steps: (1) According to the component ratio, the conductive filler, the dispersant, and the solvent are mixed and then subjected to high pressure homogenization to obtain a mixed solution; (2) According to the component ratio, the mixed solution obtained in step (1) is evenly mixed with the base resin to obtain the graphene-based conductive color paste.
7. The method for preparing a graphene-based conductive color paste according to claim 6, characterized in that: Step (1), The conductive filler is composed of graphene and other conductive fillers except graphene, and the graphene is ground; preferably, the graphene is sanded for 10 to 30 minutes with a sand mill, the speed of the sand mill is 1500 to 2500 rpm, and the sand milling solvent is water, and the type of the solvent is changed to water or N-methylpyrrolidone; and / or, The pressure of the high-pressure homogenization treatment is 100-200 MPa, preferably 120-150 MPa; and / or, The high pressure homogenization treatment time is 10 to 40 minutes, preferably 10 to 25 minutes.
8. The method for preparing a graphene-based conductive color paste according to claim 6, characterized in that: Step (2), The mixing method is high-speed shear dispersion, the rotation speed of the high-speed shear dispersion is 1200-1500 rpm, and the dispersion time is 20-40 minutes.
9. A graphene-based conductive color paste obtained by the preparation method according to any one of claims 6 to 8.
10. Use of the graphene-based conductive color paste as claimed in any one of claims 1 to 5 and 9 in antistatic coatings, conductive inks and antistatic composite materials.
Citation Information
Patent Citations
Nano aqueous conductive carbon black color paste and preparation method thereof
CN102532975A
Powder graphene as well as preparation method and application thereof
CN115231561A